Agrarian reform, cooperatives, and taxation - Aralar, Reynaldo B. (Manila, Philippines : Rex Book Store, 1980)
Since the 1980's is expected to become a decade full of great economic difficulties for peoples and governments, this edition has acquired greater relevance. Except for new developments on the subject matter, it is substantially similar to past editions which, with all humility and gratitude, has been widely accepted by both academic and non-academic sectors all over the country.
Chapter I. Cause of agrarian problems -- Chapter II. Social justice, the population explosion and agrarian reform -- Chapter III. Fundamentals of agrarian reform in the Philippines -- Chapter IV. Emancipation of tenants from the bondage of the soil -- Chapter V. The court of agrarian relations and tendency relations -- Chapter VI. The cooperative movement -- Chapter VII. Taxation in general -- Chapter VII. Fundamentals of income taxation -- Chapter IX. Income tax on individuals -- Chapter X. Income tax on corporations -- Chapter XI. Withholding on wages -- Chapter XII. Accounting periods and method of accounting -- Chapter XIII. The transfer taxes -- Chapter XIV. Specific taxes -- Chapter XV. Privilege tax on business -- Chapter XVI. The privilege taxes on occupation -- Chapter XVII. Sales taxes -- Chapter XVIII. Advance sales tax -- Chapter XIX. Compensating tax -- Chapter XX. Administrative and penal rules applicable to persons subject to privilege tax -- Chapter XXI. Amusement tax -- Chapter XXII. Fees for sealing and licensing of weights and measures -- Chapter XXIII. Customs duties -- Chapter XXIV. Residence tax -- Chapter XXV. Rights of an aggrieved taxpayer
Keywords: LAND -- TAXATION